An investigation into the level of genetic knowledge of parents of sons with Duchenne Muscular Dystrophy and their satisfaction with the genetic counselling service at Red Cross War Memorial Children's Hospital - Loggenberg, Kelly (Department of Medicine, 2014)
Includes bibliographical references (leaves 68-72 ).